Diurnal Variation in Biomarkers of Exposure to Endocrine-Disrupting Chemicals and Their Association with Oxidative Damage in Norwegian Adults: The EuroMix Study - Samuel Olushola Abimbola; Christina Xeni; Amrit Kaur Sakhi; Behzad Heibati; Trine Husøy; Hubert Dirven; Konstantinos C. Makris (Toxics, 2022)
Much evidence on the adverse health effects of endocrine-disrupting chemicals (EDCs) has accumulated during recent decades. EDCs are commonly found in various foods and personal care products (PCP). Data documenting a diurnally varying EDC metabolism in humans is scarce. This study examined (i) the time-of-day effect on the diurnal magnitude and variance of urinary biomarkers of exposure to EDCs, and (ii) the association between EDC exposures and oxidative damage in a Norwegian adult subpopulation. This was a cross-sectional panel study using biobanked samples from the EuroMix project. During a typical weekday, participants were asked to collect all day’s urine voids and record dietary and PCP habitual uses in a diary. Collected time stamps of urine voids were classified into three distinct periods in the day (morning 6 a.m.–12 p.m., mid-day 12 p.m.–6 p.m., evening 6 p.m.–6 a.m.). Questionnaires regarding demographic characteristics, personal care product usage, and dietary habits were completed. Urinary levels of EDCs (phthalates, parabens, and bisphenols) were measured using mass spectrometry and adjusted for urinary volume using specific gravity. Urinary 4-hydroxynonenal (4HNE), a lipid peroxidation marker, was measured using an immunoassay kit. Linear mixed-effect models identified EDCs under the influence of a diurnal variation effect that was adjusted for dietary habits and PCP use and examined associations between EDC and 4HNE. p-values were FDR-adjusted. Most phthalates appeared to be diurnally varying with higher urinary levels towards the evening (q < 0.001) than those measured during mid-day; this strong diurnal variation effect was not present for parabens and bisphenols. Significant (q < 0.001) positive associations were observed between all phthalates, parabens, and bisphenols (except bisphenol S) and 4HNE. This study’s findings highlighted the diurnal variation of excretion for certain EDC, but not for others, in real-life conditions. The degree of EDC chronotoxicity in distinct diurnal windows of the day warrants further investigation with longitudinal human studies.